FREE RADICAL SCAVENGING ACTIVITY OF THE BACOSIDE FRACTION FROM BACOPA MONNIERI - Mohana, Manoharan; Padma, Palghat Raghunathan (International Journal of Current Pharmaceutical Research, 2016)
Objective: Bacopa monnieri is a herb which has been used in Indian traditional medicine for a long period. Bacosides, the major constituents of Bacopa monnieri, have antioxidant, anticancer and memory enhancing properties. Methods: The bacoside fraction was isolated from the dried powder of the aerial parts of Bacopa monnieri. The free radical scavenging activity of the bacoside fraction was determined by different assays (DPPH, ABTS, SOâ—, NOâ—, OHâ— and H2O2) at concentrations ranging from 5 Âµg to 200 Âµg. Results: The scavenging activity was increased in a dose-dependent manner from 5Âµg to 50 Âµg and a plateau in activity was observed from concentrations higher than 50 Âµg of the bacoside fraction. Conclusion: Higher concentrations did not show further increase in scavenging activity. Various in vivo and in vitro studies are needed to assess the medicinal potential of the bacoside fraction